Three-phase Half-controlled Boost PFC Rectifier With New Variable Duty Cycle Control - Morais, Douglas C. [UNESP]; Seixas, Falcondes J. M. de [UNESP]; Souza, Lucas C. [UNESP]; Silva, Luciano S. C. E.; Junior, Joao C. P.; Tsuzuki, MDG; Junqueira, F. (Ieee, 2018)
Converters operating in discontinuous-conduction-mode and using the bridgeless technique can offer rectification and elevation of voltage in high frequency, also can offer better efficiency when compared to the conventional single-switch boost power-factor-correction converter. In this conduction mode, the input current naturally follows a sinusoidal envelope, dispensing current sensors of use. Some these advantages are inherent to the converter operating mode, as the zero-current-switching during the turn-on of the switches, the simplicity of control system and the lower cost. However, the discontinuous-conduction-mode operation with constant duty cycle control leads to a high harmonic content of current in low frequency, limiting the converters applications and may exceed the limits imposed by international standards. This paper presents the analysis and experimental results of the three-phase bridgeless boost converter with new variable duty cycle control, operating in discontinuous-conduction-mode. In this configuration, the current stress in semiconductors are divided and, a single pulse is necessary for switch conduction. The results proved that occurs power factor correction with harmonic current content reduction of input current in low frequency.
Keywords: Three-phase bridgeless boost converter; Power-factor-correction; Variable duty cycle control; Discontinuous-conduction-mode; Pulse-Width-Modulation